Methods in chemosensory rerearch - Simon, Sidney A. (CRC Press LLC, 2011)
Written by world experts in the field of neuronal chemoreception, Methods in Chemosensory Research describes new molecular, electrophysiological, genetic, behavioral, psychophysical, and imaging techniques that have recently been adapted to investigate the basic neuronal mechanisms underlying chemoreception: taste, olfaction and chemical-induced irritation. This unique book includes a wide variety of new and innovative imaging methods, electrophysiological methods, methods to investigate development, and various aspects of behavioral testing. Covering the entire spectrum of chemoreception, each section not only describes what information can be obtained by using each method, but also shows how to apply each method to obtain reliable results. The book presents a comprehensive view of how the brain uses information about chemical stimuli that interact with receptors in the nose and tongue. Methods in Chemosensory Research gives you the new tools to learn how chemicals affect activity from the genetic to the behavioral levels.